Several criminal, phenomenological and etiological features of criminal offences of counterfeiting money in Kosovo - Krasniqi, MSc. Milot (Iliria international review, 2012)
The Republic of Kosovo is making efforts as a young state to strengthen rule of law and efficiently combat criminality in general, and specifically organized crime, as a condition for its journey towards European integration perspectives. For a normal functioning of the economic system, the safety and protection of controlled circulation of money are of vital importance. In this direction, the state takes actions and measures to ensure that manufacturing and emissions of banknotes and bonds are undertaken by competent authorities, such as the Central Bank, and render impossible the counterfeiting of money. In Kosovo, money counterfeiting is not widely studied. Consequently, there are no recent research papers over the time when these offences have marked rather high records. This circumstance, and especially the fact that these offences are rather frequent in Kosovo, made me enter the research of this type of criminality. Apart from principles and rules stipulated by special laws of the field of economy, protection of the economic system is also helped by the Criminal Code, which incriminates the act of counterfeit money as a criminal offence against the economic system, thereby ensuring general prevention of potential offenders, and repressive measures against confirmed offenders. Protection of economic and monetary systems is also provided upon by numerous international acts. The paper is permeated by conclusions, analysis and independent recommendations, which I believe will contribute de lege ferrenda to criminal policies in preventing and combating this type of crime. In researching the criminal offences of counterfeiting money, I have used the method of historical materialism, dogmatic law method, statistical methods, surveys and interviews, and studies of individual cases. From the research of this type of crime, I have concluded that these criminal offences are a serious type of crime, which may result in major individual, family and social consequences. Nevertheless, these crimes are found in all societies, including Kosovo